Linear Active Disturbance Rejection Control Strategy of Wind-Solar Hydrogen Storage System Considering Wind Speed Variability Based on Seagull Optimization Algorithm - Gao, Jiajun; Liu, Luming; Ma, Zeyu; Li, Jiajia; Chen, Hao (2023 4th International Conference on Advanced Electrical and Energy Systems (AEES), 2023)
Considering the problems of large DC bus voltage fluctuation and weak anti-interference capability in wind-solar hybrid energy storage system, a linear active disturbance rejection control (LADRC) strategy based on the seagull optimization algorithm (SOA) is proposed. The subject of this paper is the wind-solar complementary energy storage and hydrogen production system. By introducing LADRC in the external loop voltage of the energy storage converter to solve the problem of excessive fluctuation in the output power of wind power generation systems caused by variable wind speed, so as to stabilize the DC bus voltage better.